HIV-associated peripheral neuropathies: a review - Alagoma Iyagba; Arthur Onwuchekwa (International Journal of Medical Research and Review, 2016)
Objective: To review the various neurologic complications of HIV.Methods: A MEDLINE search of the English-language literature using a combination of words (HIV, neuropathy and diagnosis) was used to identify original studies, consensus statements and reviews published in the last 25 years.Results: The various HIV-associated neuropathies are described.Conclusion: It is important for clinicians to be equipped with the knowledge of the various neuropathic complications of HIV. Prompt diagnosis of these with institution of proper treatment measures would go a long way towards reducing morbidity and mortality outcomes.